If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + -22 = 8x + 12 Reorder the terms: -22 + 10x = 8x + 12 Reorder the terms: -22 + 10x = 12 + 8x Solving -22 + 10x = 12 + 8x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-8x' to each side of the equation. -22 + 10x + -8x = 12 + 8x + -8x Combine like terms: 10x + -8x = 2x -22 + 2x = 12 + 8x + -8x Combine like terms: 8x + -8x = 0 -22 + 2x = 12 + 0 -22 + 2x = 12 Add '22' to each side of the equation. -22 + 22 + 2x = 12 + 22 Combine like terms: -22 + 22 = 0 0 + 2x = 12 + 22 2x = 12 + 22 Combine like terms: 12 + 22 = 34 2x = 34 Divide each side by '2'. x = 17 Simplifying x = 17
| x*ln(x)=(ln(3))/3 | | (x+5)*28=2x+21 | | x^2+y^2-12x+4y=24 | | x+5*28=2x+21 | | s^2+20+4s= | | 4x=44p-16 | | 4m-30+m=3m+4 | | 3(-16+7x)-15x= | | 20*(20+x)=15*(15+3x) | | 6+17(-10-8g)= | | 2q-5=7q | | 75+2=15+5 | | 11-3x+6y=0 | | P(n)=3n | | 10a-7(-17a-13)= | | (x*x)=(x-2)*(x+2) | | 21+5=15+11 | | X*12=6*(x+4) | | y=-0.2*36+50 | | 2x+53+68=75 | | k/5-9=-17 | | (x-y+2)-(x+7-2y)= | | s=250+12y | | (x*x)=x-2*x+2 | | y=2*3+2 | | x^3+12x=8x^2 | | tan7=140/x | | 8=f/4 | | 33=s-13 | | x-(x*.25)=84000 | | 4(2x-1)+3x=11 | | 6*(6+x)=5*17 |